Measuring the Role of Social Media and E-word of Mouth on Purchase Intention of Secondate Make-up Products - Sudirgo, Graciela; Cahyadi, Lukman (KINERJA, 2024)
Purchase intention is important to pay attention to because it relates to consumer interest in trying, buying, and owning products such as beauty products. Furthermore, it can be seen from the consumer's behavior of parasocial interaction, social value, and personal value towards the influencer, which will affect their interest in buying the product. This research takes the object of research as an owner as well as an influencer for beauty products Secondate. The research design uses a deductive approach with a quantitative research model to determine the impact of influencers on the quality of parasocial interaction, social values, personal values, and e-wom on purchase intention. The sample of this study were secondary make-up users with a total of 169 respondents. Data analysis used the Structural Equation Model (SEM) method. The results of the study show that parasocial interaction affects social value. Parasocial interaction increases positive perceptions of personal value, and social value can increase consumer purchase intention, but personal value cannot attract consumer purchase intention. Parasocial interaction does not affect consumer purchase intention, so e-wom does not moderate the effect of parasocial interaction on consumer purchase intention. The results of this study concluded that social media can be a means to affect the interest in buying a product. With the respondent's research on social value and personal value, it can be said that it affects a person's buying interest in a product. Social value and personal value can help us to sort out which products we need and which are suitable for us.